Estrutura populacional e aspectos reprodutivos do Octopus insularis Cephalopodas: Octopodidae: implicações para o manejo da pesca de polvo no município de Rio de Fogo-RN - Lima, Françoise Dantas de (2012)
In northeastern Brazil, Octopus insularis is the most commercially important cephalopod species and its capture has been performed for several years by the lobster fishermen in the region. In order to obtain information about the reproductive biology, 1108 specimens were collected between November 2009 and September 2011 in the landings and fish markets of Rio do Fogo (RN). For each specimen the mantle length (CM) and total fresh weight (PT) were recorded. Gonads of 264 males and 295 females were examined macroscopically and histologically to assess sexual maturation and determine reproductive indices. Four reproductive stages were determined for males (immature, maturing, mature and post-mature) and females (immature, early maturing, late maturing and mature). The average of eggs recorded in the female s gonads was 93.820 and 39 was the average of spermatophores found in male Needham s complex. Spermathecae with sperm were found in females with 69 mm CM (immature). Males and females become sexually mature at 64.41 and 98.50 mm of CM, respectively. The weight at sexual maturity was 270 g for males and 630 g for females. The values of the size and weight at sexual maturity found in this study show that males mature at smaller sizes than females. For both sexes the maturation peaks occurred in February and November 2010 and also in September 2011. The periods of maximum reproductive activity lasted about 3 months and it seems to occur every 7 10 months. Only one spent female (stage V) was found and the number of mature females was low. Presumably, mature females migrate to deep waters with complex habitat to protect the offspring, indicating that fishery by snorkeling with maximum depth of 15 meters is not reaches this part of the stock. Finally, it is noticeable the importance of the establishment of management strategies for the exploitation of O. insularis different of the ones used for O. vulgaris, once the species have distinct biological features